Liability of legal entities for tax offenses: experience of foreign countries - M. Balyshev (Науковий вісник Ужгородського національного університету. Серія Право, 2024)
The article is devoted to highlighting the experience of foreign countries regarding responsibility for tax offenses. It is noted that since the filling of the budget of any state depends on establishing a mechanism of control over the implementation of tax revenues from large taxpayers, namely from legal entities, the question arises of introducing legal responsibility for such entities for violation of established prescriptions. One of the tools to combat tax evasion in Europe is the standard tax justice model, which introduces several sanctions for legal entities that violate tax legislation.